Investigations on Monthly Wind Erosion Climatic Factor over Karnataka State, India - Ramachandran, V S (Annals of Arid Zone, 2016)
The mean monthly local wind erosion climatic factor (C) was computed on monthly basis and its distribution pattern over Karnataka State lit various geographical locations is described. It was found that the C factor varied from high to very high intensity over north-interior and eastern portion of south-interior Karnataka, moderate to low intensity over westward side of the south-interior and very low intensity over coastal Karnataka State. The highest and lowest values of C factor were noticed during the months of June and October, respectively, while the corresponding coefficient of variation in March and June. The C factor was found to have the highest intensity over the State during the south-west monsoon season while the lowest intensity was during early part of summer and later part of winter seasons.